2008
DOI: 10.1002/ejoc.200800836
|View full text |Cite
|
Sign up to set email alerts
|

(Cycloheptyne)dicobalt Complexes in Organic Synthesis

Abstract: Cobalt complexes of cycloheptynes are thermally stable compounds, unlike their metal‐free counterparts. The past decade has seen the development of a number of reliable methods for their preparation, and a substantial delineation of the reactions they undergo and tolerate. In turn, these developments have resulted in the exploitation of cycloheptynedicobalt complexes in synthesis. This review details the recent developments in the chemistry of these compounds. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…In the dibenzosuberenyl system,t he aromatic cation is at least partially transformed into the intrinsically less stable cross-conjugated dibenzoheptafulvene, which becomes energetically favoured when strongly bonded to the cluster. In contrast, the previously studied antiaromatic fluorenyl, indenyl and cyclopentadienyl cluster-stabilised cations, 10, 11 and 12, might be considered as developing pentafulvenec haracter thus losing their antiaromatic character.I nterestingly,i nt he course of his elegant studies of the synthetic utility of cycloheptyne-dicobalt clusters, [48] Green showedt hat the [Co 2 (CO) 6 (dehydrotropylium)] + cation is only weakly aromatic. [49] Furthermore, we note that the effecto fat ricarbonylchromium fragment on the thermodynamic stability of benzylc ations was investigated many years ago by Ceccon et al [50] It was shown from pK R + measurements that incorporation of the [Cr(CO) 3 ]g roup can render the complexed cation more, or less, stable than the correspondingf ree ion, and is dependent on both electronic and conformational effects.…”
Section: Computational Approachmentioning
confidence: 99%
“…In the dibenzosuberenyl system,t he aromatic cation is at least partially transformed into the intrinsically less stable cross-conjugated dibenzoheptafulvene, which becomes energetically favoured when strongly bonded to the cluster. In contrast, the previously studied antiaromatic fluorenyl, indenyl and cyclopentadienyl cluster-stabilised cations, 10, 11 and 12, might be considered as developing pentafulvenec haracter thus losing their antiaromatic character.I nterestingly,i nt he course of his elegant studies of the synthetic utility of cycloheptyne-dicobalt clusters, [48] Green showedt hat the [Co 2 (CO) 6 (dehydrotropylium)] + cation is only weakly aromatic. [49] Furthermore, we note that the effecto fat ricarbonylchromium fragment on the thermodynamic stability of benzylc ations was investigated many years ago by Ceccon et al [50] It was shown from pK R + measurements that incorporation of the [Cr(CO) 3 ]g roup can render the complexed cation more, or less, stable than the correspondingf ree ion, and is dependent on both electronic and conformational effects.…”
Section: Computational Approachmentioning
confidence: 99%
“…Increasing the amount of propargyl alcohol/ether-Co 2 (CO) 6 complex 6a-e to slightly over two equivalents enabled, in most cases, ready conversion of 2,7-dimethoxynaphthalene (5a) to disubstituted products (9-10) ( Table 2). In these cases, a competition existed between the formation of 1,8-disubstitution products (9) and 1,6-disubtitution products (10), which depended upon the structure of the Nicholas reaction precursor complex 6. In the case of unsubstituted 6a, 1,8-disubstitution predominated, although not to the exclusion of 1, 6-disubstitution (9a, 63%, 10a, 9%).…”
Section: Introductionmentioning
confidence: 99%
“…By using reductive decomplexation conditions, the cobalt carbonyl moiety can be removed without ring rupture caused by bond strain. Green has aptly reviewed the application of cycloheptyne-dicobalt carbonyl complexes in synthesis [32], and also applied this strategy towards the total synthesis of allocolchicines [33,34], of interest because several members of this class of alkaloids show anticancer properties. The synthesis of the parent compound, (-)-allocolchicine, is depicted in Scheme 11.…”
Section: Alkaloidsmentioning
confidence: 99%